High-strength wear-resistant fire-resistant plate and preparation method thereof
Patent Information
- Application Number
- CN202611389492.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-08
- Publication Date
- 2026-10-09
AI Technical Summary
现有普通承烧板多采用刚玉、莫来石、堇青石或碳化硅等陶瓷原料制备,虽然能够满足一般烧成条件下的支承需求,但在高负荷、高温差和高磨耗工况下仍容易出现表面磨损、边角崩裂、微裂纹扩展、板面剥落和高温变形等问题
[0026](1)本发明以烧结刚玉和电熔莫来石颗粒作为承载骨架,配合α-氧化铝微粉、碳化硅微粉、氧化锆微粉和钛酸铝粉,使承烧板烧结后具有稳定的陶瓷结构。烧结刚玉提高板体承载能力,电熔莫来石颗粒提高高温使用稳定性,α-氧化铝微粉填充颗粒间隙并促进烧结结合,碳化硅微粉提高板面耐磨能力,氧化锆微粉降低裂纹继续扩展的风险,钛酸铝粉缓冲升温和冷却过程中的热应力,因此所得高强度耐磨承烧板在高温承载和反复热循环条件下不易出现开裂、剥落和变形。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention belongs to the field of high-temperature kiln furniture ceramic materials technology, specifically relating to a high-strength wear-resistant firing plate and its preparation method. Background Technology
[0002] Firing plates are crucial kiln furniture materials used in high-temperature kilns to support the green body, transfer heat, and maintain the shape stability of the fired products. They are widely used in the firing processes of electronic ceramics, structural ceramics, functional powders, refractories, powder metallurgy, and new energy materials. With increasing firing temperatures, loading densities, and frequency of use, firing plates not only need to withstand the weight of the green body itself and the impact of loading and unloading, but also need to endure the combined effects of high-temperature atmospheres, rapid heating and cooling, friction from kiln cars or rollers, and volatile components from the fired products over long periods. Existing common firing plates are mostly made from ceramic raw materials such as corundum, mullite, cordierite, or silicon carbide. While these materials can meet the support requirements under general firing conditions, they are still prone to surface wear, edge chipping, microcrack propagation, plate peeling, and high-temperature deformation under high load, high temperature difference, and high abrasion conditions.
[0003] Corundum-based sintering plates possess high refractoriness and mechanical strength, but their relatively large thermal expansion makes them prone to cracking due to thermal stress concentration during repeated heating and cooling. Mullite-based sintering plates exhibit good high-temperature stability and creep resistance, but their densification and wear resistance still have room for improvement when used alone. Silicon carbide materials have good thermal conductivity and strong wear resistance, but they are prone to surface oxidation during long-term use in oxygen-containing atmospheres and at high temperatures, leading to changes in interface structure and a decline in mechanical properties. Aluminum titanate materials have low thermal expansion characteristics and can buffer thermal shock stress, but their own strength and sintering stability are limited. Therefore, relying solely on a single ceramic phase or conventional composite aggregates makes it difficult to simultaneously achieve multiple performance requirements such as high strength, wear resistance, thermal shock resistance, and high-temperature dimensional stability.
[0004] Furthermore, current sintering plate preparation processes often rely on mixing ordinary binders and conventional powders, resulting in insufficient interfacial bonding between powders. This leads to a relatively simple grain boundary structure after firing, making microcracks prone to propagate along grain boundaries under thermal shock or abrasion, thus shortening the lifespan of the sintering plate. For composite systems containing corundum, mullite, silicon carbide, zirconium oxide, and aluminum titanate, further controlling grain matching, interfacial bonding, and crack deflection during sintering is crucial for improving the overall performance of the sintering plate. Especially under conditions of repeated high-temperature use, the sintering plate needs to form a stable load-bearing skeleton, a thermal shock buffer structure, and a wear-resistant pinning structure to reduce particle shedding and crack propagation. Therefore, developing a high-strength, wear-resistant sintering plate prepared through the synergistic effect of composite ceramic powder, thermally shock-stabilized crystalline phases, pinned toughening whiskers, and a composite bonding and dispersion system has significant practical application value. Summary of the Invention
[0005] To address the shortcomings of existing technologies, the present invention aims to provide a high-strength wear-resistant sintering plate and its preparation method.
[0006] In a first aspect, the present invention provides a method for preparing a high-strength, wear-resistant sintered plate, comprising the following steps:
[0007] S1. By weight, mix 35.0-50.0 parts sintered corundum, 18.0-28.0 parts fused mullite particles, 8.0-15.0 parts α-alumina micro powder, 6.0-12.0 parts silicon carbide micro powder, 3.0-8.0 parts zirconium oxide micro powder, 3.0-7.0 parts aluminum titanate powder, 3.0-8.0 parts calcined kaolin, 2.0-5.0 parts talc powder, and 0.5-2.0 parts magnesium oxide powder to obtain basic ceramic powder; add 2.0-6.0 parts yttrium cerium zirconium aluminum silicon thermal shock stabilized crystalline phase and 1.5-5.0 parts boron titanium silicon to the basic ceramic powder. Carbon nails are used to toughen whiskers, and mixing continues to obtain composite ceramic powder. 0.4-1.2 parts of polyvinyl alcohol are added to 8.0-16.0 parts of deionized water and stirred at 85-95℃. After cooling to room temperature, 4.0-9.0 parts of silica sol are added while stirring, and stirring continues. Then, 0.2-0.8 parts of sodium carboxymethyl cellulose, 0.5-1.5 parts of polyethylene glycol 400, and 0.1-0.5 parts of sodium polyacrylate are added and stirred to obtain a composite binder dispersion. The composite ceramic powder is added to the composite binder dispersion and mixed at 20-30℃ to form a clay, yielding a ceramic blank.
[0008] S2. Press the ceramic blank into shape, dry it to obtain the firing plate blank; place the firing plate blank in the kiln, heat it to 300-400℃ in air atmosphere and hold it; carry out pre-reaction treatment and sintering treatment in argon atmosphere, and then cool it.
[0009] The method for preparing the thermally shock-stabilized yttrium cerium zirconium aluminum silicon crystalline phase includes:
[0010] A1. By weight, add 4.0-8.0 parts of yttrium hexahydrate, 6.0-12.0 parts of zirconium oxychloride octahydrate, 3.0-7.0 parts of cerium nitrate hexahydrate, and 12.0-20.0 parts of aluminum nitrate nonahydrate to 15.0-25.0 parts of deionized water and stir to obtain an aqueous solution of the metal salt; add 4.0-9.0 parts of tetraethyl orthosilicate to 20.0-35.0 parts of anhydrous ethanol and stir to obtain an alcoholic solution of tetraethyl orthosilicate; add the alcoholic solution of tetraethyl orthosilicate to the aqueous solution of the metal salt and stir to obtain a precursor solution; add 8.0-15.0 parts of citric acid and 10.0-18.0 parts of ethylene glycol to the precursor solution and stir at 70-85℃; adjust the pH to 6.0-8.0 with ammonia water and continue stirring to obtain a yttrium-cerium-zirconium-aluminum-silicon composite gel;
[0011] A2. Dry the yttrium cerium zirconium aluminum silicon composite gel at 100-120℃ to obtain a dry gel; heat the dry gel to 450-550℃ in air atmosphere and keep it at that temperature, then heat it to 950-1100℃ and keep it at that temperature, cool it to room temperature, ball mill it, and sieve it.
[0012] In this invention, during the preparation of the thermally shock-stabilized yttrium-cerium-zirconium-aluminum-silicon crystalline phase, yttrium nitrate hexahydrate, zirconium oxychloride octahydrate, cerium nitrate hexahydrate, and aluminum nitrate nonahydrate are dissolved in deionized water to obtain an aqueous solution of metal salts containing yttrium, cerium, zirconium, and aluminum. The metal ions are dispersed in the aqueous phase, providing a source of yttrium, cerium, zirconium, and aluminum for the subsequent composite system. Tetraethyl orthosilicate dissolves in anhydrous ethanol to form an tetraethyl orthosilicate alcoholic solution. After the addition of the metal salt aqueous solution, tetraethyl orthosilicate gradually undergoes hydrolysis and condensation in the coexistence of water and ethanol. The silicon component gradually transforms from its original organosilicon precursor form into a silicon-oxygen network, interweaving with the metal components in the aqueous phase. After citric acid is added to the precursor fluid, its carboxyl groups undergo complexation with the yttrium, cerium, zirconium, and aluminum components, uniformly binding the metal components within the complex structure and reducing localized agglomeration of each metal component. Upon addition of ethylene glycol, an esterification reaction occurs with the carboxyl groups of citric acid, accompanied by polymerization, further fixing the complexed metal components within the organic macromolecular network. Adjusting the system's pH with ammonia water reduces the acidity, facilitating the continued hydrolysis and condensation of tetraethyl orthosilicate. Simultaneously, the entire organometallic complex network transforms into a yttrium-cerium-zirconium-aluminum-silicon composite gel under the influence of gradual water migration and condensation. The yttrium-cerium-zirconium-aluminum-silicon composite gel is dried at low temperature to obtain a dry gel. Upon further heating of the dry gel in air, the organic complex framework and nitrate ions decompose and release gases. The yttrium, cerium, zirconium, aluminum, and silicon components come into contact with each other at the nanoscale and undergo solid-phase rearrangement, ultimately yielding a uniformly composed, thermally shock-stable yttrium-cerium-zirconium-aluminum-silicon crystalline phase.
[0013] The method for preparing the boron-titanium-silicon-carbon pinned toughened whiskers includes:
[0014] B1. By weight, mix 8.0-16.0 parts of tetrabutyl titanate, 20.0-35.0 parts of anhydrous ethanol and 2.0-5.0 parts of acetylacetone, and stir to obtain a titanium complex solution; mix 6.0-12.0 parts of boric acid, 5.0-10.0 parts of nano-silica, 3.0-7.0 parts of acetylene black, 6.0-14.0 parts of anhydrous glucose and 6.0-12.0 parts of deionized water to obtain a borosilicate carbon dispersion; add the borosilicate carbon dispersion to the titanium complex solution and stir at 45-60℃ to obtain a borosilicate carbon composite sol.
[0015] B2. Dry and grind the boron-titanium-silicon-carbon composite sol to obtain precursor powder; mix the precursor powder with 8.0-15.0 parts of sodium chloride, 8.0-15.0 parts of potassium chloride and 0.5-1.5 parts of sodium fluoride, heat to 1400-1450℃ under argon atmosphere and hold at that temperature, cool to room temperature, wash with deionized water, dry, ball mill and sieve.
[0016] In this invention, during the preparation of boron-titanium-silicon-carbon pinned toughened whiskers, tetrabutyl titanate is first mixed with anhydrous ethanol and acetylacetone. The carbonyl component of acetylacetone complexes with the titanium centers of tetrabutyl titanate, reducing the tendency of tetrabutyl titanate to rapidly hydrolyze in water, resulting in a relatively uniformly dispersed titanium complex solution. Boric acid, nano-silica, acetylene black, anhydrous glucose, and deionized water are mixed to obtain a boron-silicon-carbon dispersion, wherein boric acid provides the boron-oxygen component, nano-silica provides the silicon-oxygen component, acetylene black provides a stable solid carbon source, and anhydrous glucose is converted into a supplementary dispersed carbon source during subsequent drying and heating. After the boron-silicon-carbon dispersion is added to the titanium complex solution, the water in the system promotes the controlled hydrolysis of tetrabutyl titanate. The titanium hydrolysis products are tightly cross-linked with boric acid, nano-silica, acetylene black, and anhydrous glucose to obtain a boron-titanium-silicon-carbon composite sol. This composite sol is not a clear, single solution, but rather a dispersed precursor system containing nano-silica and acetylene black, ensuring that the boron, titanium, silicon, and carbon components remain in close contact after drying. The boron-titanium-silicon-carbon composite sol is dried and ground to obtain a precursor powder, which is then mixed with sodium chloride, potassium chloride, and sodium fluoride. When heated under an argon atmosphere, the sodium chloride, potassium chloride, and sodium fluoride form a molten salt environment, accelerating the migration and rearrangement of the boron, titanium, silicon, and carbon components. The titanium hydrolysis products undergo a boron-carbothermic reduction reaction with the boron-oxygen components released from boric acid and the carbon source, while the nano-silica undergoes a carbothermic reduction reaction with the carbon source. Simultaneously, needle-like structures containing boron-titanium and silicon-carbon grow within the system. After washing with deionized water to remove residual soluble salts, the remaining material is dried, ball-milled, and sieved to obtain boron-titanium-silicon-carbon pinned toughened whiskers.
[0017] In this invention, during the preparation of the high-strength wear-resistant sintered plate, sintered corundum serves as the main load-bearing phase, and fused mullite particles act as a high-temperature stable framework, forming the basic framework structure. α-alumina micropowder fills the pores between the sintered corundum and fused mullite particles, promoting the formation of connecting necks at particle contact points during heating, thus improving the matrix density. Silicon carbide micropowder possesses high hardness and thermal conductivity, enhancing the wear resistance of the plate surface and alleviating thermal stress. Zirconia micropowder can inhibit further crack penetration. Aluminum titanate powder exhibits low thermal expansion, buffering thermal stress during the heating and cooling process of the sintered plate. Calcined kaolin, talc, and magnesium oxide powder participate in the reaction between the aluminum, silicon, and magnesium components, improving grain boundary bonding. Yttrium, cerium, zirconium, aluminum, and silicon thermal shock stabilizing crystalline phases are distributed between the composite ceramic particles, enhancing the thermal shock resistance of the sintered plate. Boron, titanium, silicon, and carbon pinning toughening whiskers are distributed at the particle interface and near the micropores of the plate, forming bridging and pinning structures, reducing particle shedding during use. Polyvinyl alcohol, silica sol, sodium carboxymethyl cellulose, polyethylene glycol 400, sodium polyacrylate, and deionized water form a composite binder dispersion, giving the composite ceramic powder good plasticity and uniform dispersion before pressing. The sintered plate blank is first treated at low temperature in an air atmosphere to remove organic components, then undergoes pre-reaction and sintering treatments in an argon atmosphere. The inert atmosphere protects the silicon carbide micropowder and boron-titanium-silicon-carbon pinned toughening whiskers from oxidation and loss. After sintering and cooling, a composite ceramic structure is formed inside the sintered plate, consisting of sintered corundum, fused mullite particles, yttrium-cerium-zirconium-aluminum-silicon thermally shock-stabilized crystalline phases, and boron-titanium-silicon-carbon pinned toughening whiskers. This results in a high-strength, wear-resistant sintered plate that combines high strength, wear resistance, thermal shock resistance, and high-temperature dimensional stability.
[0018] According to a preferred embodiment of the present invention, in step S1, the stirring time at 85-95°C is 30-60 min.
[0019] According to a preferred embodiment of the present invention, in step S2, the pre-reaction treatment includes: heating to 700-900°C and holding, then heating to 1250-1350°C and holding; the sintering treatment includes: heating to 1450-1580°C and holding.
[0020] According to a preferred embodiment of the present invention, in step A1, the stirring time at 70-85°C is 2-4 hours.
[0021] According to a preferred embodiment of the present invention, in step A2, the holding time for heating to 450-550°C is 1-3 hours; the holding time for heating to 950-1100°C is 2-4 hours.
[0022] According to a preferred embodiment of the present invention, in step B1, the stirring time at 45-60°C is 1-3 hours.
[0023] According to a preferred embodiment of the present invention, in step B2, the time for holding the temperature at 1400-1450°C is 2-5 hours.
[0024] In a second aspect, the present invention provides a high-strength wear-resistant sintering plate prepared according to the method described above.
[0025] Compared with the prior art, the present invention has the following beneficial effects:
[0026] (1) This invention uses sintered corundum and fused mullite particles as the load-bearing skeleton, combined with α-alumina micro powder, silicon carbide micro powder, zirconium oxide micro powder and aluminum titanate powder, so that the sintered plate has a stable ceramic structure. Sintered corundum improves the load-bearing capacity of the plate, fused mullite particles improve the stability of high-temperature use, α-alumina micro powder fills the gaps between particles and promotes sintering bonding, silicon carbide micro powder improves the wear resistance of the plate surface, zirconium oxide micro powder reduces the risk of crack propagation, and aluminum titanate powder buffers the thermal stress during heating and cooling. Therefore, the resulting high-strength wear-resistant sintered plate is not prone to cracking, peeling and deformation under high-temperature load and repeated thermal cycling conditions.
[0027] (2) The present invention adds yttrium cerium zirconium aluminum silicon thermal shock stabilizing crystalline phase and boron titanium silicon carbon pinning toughening whiskers to the basic ceramic powder. The yttrium cerium zirconium aluminum silicon thermal shock stabilizing crystalline phase is distributed at the particle interface, which can improve the interfacial stability between sintered corundum, fused mullite particles, α-alumina micro powder, silicon carbide micro powder, zirconium oxide micro powder and aluminum titanate powder, and reduce thermal stress concentration; the boron titanium silicon carbon pinning toughening whiskers are distributed in the interparticle gaps and near the micropores, which can form bridging and pinning effects inside the plate, reduce the possibility of particle shedding during wear, thereby improving the crack resistance, wear resistance and service life of the high-strength wear-resistant sintered plate.
[0028] (3) This invention uses polyvinyl alcohol, deionized water, silica sol, sodium carboxymethyl cellulose, polyethylene glycol 400, and sodium polyacrylate to prepare a composite binder dispersion, which keeps the composite ceramic powder uniformly dispersed during mixing and kneading, and gives the ceramic blank suitable adhesion and molding plasticity, reducing cracks and density differences in the drying process of the sintered plate blank. The sintered plate blank is first subjected to low-temperature treatment in an air atmosphere, and then pre-reaction treatment and sintering treatment in an argon atmosphere, which can reduce the oxidation loss of silicon carbide micro powder and boron-titanium-silicon-carbon pinned toughening whiskers, so that the final high-strength wear-resistant sintered plate has strength, wear resistance, thermal shock resistance and high-temperature dimensional stability. Detailed Implementation
[0029] To facilitate understanding of the present invention, the following embodiments are provided. Those skilled in the art should understand that these embodiments are merely illustrative and should not be construed as limiting the scope of the invention.
[0030] Example 1
[0031] This embodiment provides a method for preparing a high-strength, wear-resistant sintered plate, the steps of which include:
[0032] Step S1: Weigh 42.5g sintered corundum, 23.0g fused mullite particles, 11.5g α-alumina micro powder, 9.0g silicon carbide micro powder, 5.5g zirconium oxide micro powder, 5.0g aluminum titanate powder, 5.5g calcined kaolin, 3.5g talc powder, and 1.25g magnesium oxide powder, and mix for 30min to obtain basic ceramic powder; add 4.0g yttrium cerium zirconium aluminum silicon thermal shock stabilized crystal phase and 3.25g boron titanium silicon carbon pinned toughening whiskers to the basic ceramic powder, and continue mixing for 30min to obtain composite. Ceramic powder; 0.8g polyvinyl alcohol was added to 12.0g deionized water and stirred at 90℃ for 45min. After cooling to 25℃, 6.5g silica sol was added while stirring, and stirring was continued for 20min. Then, 0.5g sodium carboxymethyl cellulose, 1.0g polyethylene glycol 400 and 0.3g sodium polyacrylate were added, and stirring was continued for 30min to obtain a composite binder dispersion. The composite ceramic powder was added to the composite binder dispersion and mixed at 25℃ for 40min. The mixture was then kneaded for 20min to obtain a ceramic blank.
[0033] Step S2: Place the ceramic blank in a mold and press it into shape. The molding pressure is 25 MPa and the holding time is 60 s to obtain a wet blank with a length of 120 mm, a width of 80 mm and a thickness of 10 mm. Let the wet blank stand at 25°C for 12 h, and then dry it at 110°C for 8 h to obtain the firing plate blank. Place the firing plate blank in a high-temperature kiln and heat it to 350°C for 2 h in an air atmosphere. Then switch to an argon atmosphere, heat it to 800°C for 2 h, then heat it to 1300°C for 3 h, then heat it to 1515°C for 4 h, and cool it to obtain a high-strength wear-resistant firing plate.
[0034] Preparation steps of yttrium cerium zirconium aluminum silicon thermally shock-stabilized crystalline phase:
[0035] Step A1: Weigh 6.0g of yttrium nitrate hexahydrate, 9.0g of zirconium oxychloride octahydrate, 5.0g of cerium nitrate hexahydrate, and 16.0g of aluminum nitrate nonahydrate and add them to 20.0g of deionized water. Stir for 30min to fully disperse the yttrium nitrate hexahydrate, zirconium oxychloride octahydrate, cerium nitrate hexahydrate, and aluminum nitrate nonahydrate to obtain an aqueous solution of the metal salt. Weigh 6.5g of tetraethyl orthosilicate and add it to 27.5g of anhydrous ethanol. Stir for 20min to obtain an alcoholic solution of tetraethyl orthosilicate. Add the alcoholic solution of tetraethyl orthosilicate to the aqueous solution of the metal salt and stir for 30min to obtain a precursor solution. Add 11.5g of citric acid and 14.0g of ethylene glycol to the precursor solution and stir at 77.5℃ for 3h. Adjust the pH to 7.0 with ammonia and continue stirring for 40min to obtain a yttrium-cerium-zirconium-aluminum-silicon composite gel.
[0036] Step A2: Place the yttrium cerium zirconium aluminum silicon composite gel in a dry container and dry it at 110°C for 8 hours to obtain a dry gel; place the dry gel in a heat-resistant crucible and heat it to 500°C for 2 hours in an air atmosphere, then heat it to 1025°C for 3 hours and cool it to room temperature to obtain a calcined product; ball mill the calcined product for 4 hours and pass it through a 75μm sieve to obtain a thermally shock-stable yttrium cerium zirconium aluminum silicon crystalline phase.
[0037] Preparation steps of boron-titanium-silicon-carbon pinned toughened whiskers:
[0038] Step B1: Weigh 12.0g tetrabutyl titanate, 27.5g anhydrous ethanol and 3.5g acetylacetone, mix and stir for 30min to obtain a titanium complex solution; weigh 9.0g boric acid, 7.5g nano silica, 5.0g acetylene black, 10.0g anhydrous glucose and 9.0g deionized water, mix and stir for 40min to obtain a borosilicate carbon dispersion; add the borosilicate carbon dispersion to the titanium complex solution and stir at 52.5℃ for 2h to obtain a borosilicate carbon composite sol.
[0039] Step B2: Dry the boron-titanium-silicon-carbon composite sol at 110℃ for 8 hours and grind it for 30 minutes to obtain precursor powder; mix the precursor powder with 11.5g sodium chloride, 11.5g potassium chloride and 1.0g sodium fluoride for 30 minutes, place it in a heat-resistant crucible, heat it to 1425℃ and hold it for 3.5 hours under an argon atmosphere, and cool it to room temperature to obtain molten salt treated product; wash the molten salt treated product with deionized water 5 times, each time using 100mL of deionized water, dry it at 110℃ for 6 hours after washing, ball mill it for 3 hours, and pass it through a 75μm sieve to obtain boron-titanium-silicon-carbon pinned toughened whiskers.
[0040] Example 2
[0041] The difference between this embodiment and Embodiment 1 is that this embodiment provides a method for preparing a high-strength wear-resistant sintered plate, the steps of which include:
[0042] Step S1: Weigh 35.0g of sintered corundum, 18.0g of fused mullite particles, 8.0g of α-alumina micro powder, 6.0g of silicon carbide micro powder, 3.0g of zirconium oxide micro powder, 3.0g of aluminum titanate powder, 3.0g of calcined kaolin, 2.0g of talc powder, and 0.5g of magnesium oxide powder and mix them to obtain basic ceramic powder; add 2.0g of yttrium cerium zirconium aluminum silicon thermal shock stabilized crystal phase and 1.5g of boron titanium silicon carbon pinned toughening whiskers to the basic ceramic powder, and continue mixing to obtain... Composite ceramic powder; 0.4g polyvinyl alcohol was added to 8.0g deionized water and stirred at 85℃ for 30min. After cooling to room temperature, 4.0g silica sol was added while stirring. 0.2g sodium carboxymethyl cellulose, 0.5g polyethylene glycol 400 and 0.1g sodium polyacrylate were added and stirred until the system was homogeneous to obtain a composite binder dispersion; the composite ceramic powder was added to the composite binder dispersion and mixed at 20℃. The mixture was then kneaded to obtain a ceramic blank.
[0043] Step S2: Press the ceramic blank into shape, dry it to obtain the firing plate blank; place the firing plate blank in a high-temperature kiln, heat it to 300℃ and hold it in an air atmosphere; heat it to 700℃ and hold it in an argon atmosphere, then heat it to 1250℃ and hold it, then heat it to 1450℃ and hold it, then cool it to obtain a high-strength wear-resistant firing plate.
[0044] Preparation steps of yttrium cerium zirconium aluminum silicon thermally shock-stabilized crystalline phase:
[0045] Step A1: Weigh 4.0g of yttrium nitrate hexahydrate, 6.0g of zirconium oxychloride octahydrate, 3.0g of cerium nitrate hexahydrate, and 12.0g of aluminum nitrate nonahydrate, and add them to 15.0g of deionized water. Stir until the metal salts are fully dispersed and form an aqueous solution of the metal salts. Weigh 4.0g of tetraethyl orthosilicate and add it to 20.0g of anhydrous ethanol. Stir until a tetraethyl orthosilicate alcohol solution is formed. Add the tetraethyl orthosilicate alcohol solution to the aqueous solution of the metal salts and stir until the system is homogeneous to obtain the precursor solution. Add 8.0g of citric acid and 10.0g of ethylene glycol to the precursor solution and stir at 70℃ for 2 hours. Adjust the pH to 6.0 with ammonia water and continue stirring until a homogeneous gel is formed to obtain the yttrium-cerium-zirconium-aluminum-silicon composite gel.
[0046] Step A2: Dry the yttrium cerium zirconium aluminum silicon composite gel at 100°C to obtain a dry gel; heat the dry gel to 450°C and hold for 1 hour in air atmosphere, then heat it to 950°C and hold for 2 hours, cool it to room temperature, ball mill it, and sieve it to obtain the thermally shock-stable yttrium cerium zirconium aluminum silicon crystalline phase.
[0047] Preparation steps of boron-titanium-silicon-carbon pinned toughened whiskers:
[0048] Step B1: Weigh 8.0g tetrabutyl titanate, 20.0g anhydrous ethanol and 2.0g acetylacetone and mix them until a uniform titanium complex solution is formed; weigh 6.0g boric acid, 5.0g nano silica, 3.0g acetylene black, 6.0g anhydrous glucose and 6.0g deionized water and mix them until a borosilicate carbon dispersion is formed; add the borosilicate carbon dispersion to the titanium complex solution and stir at 45℃ for 1h to obtain borosilicate carbon composite sol;
[0049] Step B2: Dry and grind the boron-titanium-silicon-carbon composite sol to obtain precursor powder; mix the precursor powder with 8.0g sodium chloride, 8.0g potassium chloride and 0.5g sodium fluoride, heat to 1400℃ and hold for 2h under argon atmosphere, cool to room temperature, wash with deionized water, dry, ball mill and sieve to obtain boron-titanium-silicon-carbon pinned toughened whiskers.
[0050] Example 3
[0051] The difference between this embodiment and Embodiment 1 is that this embodiment provides a method for preparing a high-strength wear-resistant sintered plate, the steps of which include:
[0052] Step S1: Weigh 50.0g of sintered corundum, 28.0g of fused mullite particles, 15.0g of α-alumina micro powder, 12.0g of silicon carbide micro powder, 8.0g of zirconium oxide micro powder, 7.0g of aluminum titanate powder, 8.0g of calcined kaolin, 5.0g of talc powder, and 2.0g of magnesium oxide powder and mix them to obtain basic ceramic powder; add 6.0g of yttrium cerium zirconium aluminum silicon thermal shock stabilized crystal phase and 5.0g of boron titanium silicon carbon pinned toughening whiskers to the basic ceramic powder, and continue mixing to obtain... To obtain composite ceramic powder; add 1.2g polyvinyl alcohol to 16.0g deionized water, stir at 95℃ for 60min, cool to room temperature, add 9.0g silica sol while stirring, continue stirring, add 0.8g sodium carboxymethyl cellulose, 1.5g polyethylene glycol 400 and 0.5g sodium polyacrylate, stir until the system is uniform to obtain a composite binder dispersion; add composite ceramic powder to the composite binder dispersion, mix at 30℃, knead into a paste to obtain ceramic blank;
[0053] Step S2: Press the ceramic blank into shape, dry it to obtain the firing plate blank; place the firing plate blank in a high-temperature kiln, heat it to 400℃ and hold it in an air atmosphere; heat it to 900℃ and hold it in an argon atmosphere, then heat it to 1350℃ and hold it, then heat it to 1580℃ and hold it, then cool it to obtain a high-strength wear-resistant firing plate.
[0054] Preparation steps of yttrium cerium zirconium aluminum silicon thermally shock-stabilized crystalline phase:
[0055] Step A1: Weigh 8.0g of yttrium nitrate hexahydrate, 12.0g of zirconium oxychloride octahydrate, 7.0g of cerium nitrate hexahydrate, and 20.0g of aluminum nitrate nonahydrate, and add them to 25.0g of deionized water. Stir until the metal salts are fully dispersed and form an aqueous solution of the metal salts. Weigh 9.0g of tetraethyl orthosilicate and add it to 35.0g of anhydrous ethanol. Stir until a tetraethyl orthosilicate alcohol solution is formed. Add the tetraethyl orthosilicate alcohol solution to the aqueous solution of the metal salts and stir until the system is homogeneous to obtain the precursor solution. Add 15.0g of citric acid and 18.0g of ethylene glycol to the precursor solution and stir at 85℃ for 4 hours. Adjust the pH to 8.0 with ammonia and continue stirring until a homogeneous gel is formed to obtain the yttrium-cerium-zirconium-aluminum-silicon composite gel.
[0056] Step A2: Dry the yttrium cerium zirconium aluminum silicon composite gel at 120°C to obtain a dry gel; heat the dry gel to 550°C and hold for 3 hours in air atmosphere, then heat it to 1100°C and hold for 4 hours, cool it to room temperature, ball mill it, and sieve it to obtain the thermally shock-stable yttrium cerium zirconium aluminum silicon crystalline phase.
[0057] Preparation steps of boron-titanium-silicon-carbon pinned toughened whiskers:
[0058] Step B1: Weigh 16.0g tetrabutyl titanate, 35.0g anhydrous ethanol and 5.0g acetylacetone and mix them together, stirring until a uniform titanium complex solution is formed; weigh 12.0g boric acid, 10.0g nano silica, 7.0g acetylene black, 14.0g anhydrous glucose and 12.0g deionized water and mix them together, stirring until a borosilicate carbon dispersion is formed; add the borosilicate carbon dispersion to the titanium complex solution and stir at 60℃ for 3h to obtain a borosilicate carbon composite sol;
[0059] Step B2: Dry and grind the boron-titanium-silicon-carbon composite sol to obtain precursor powder; mix the precursor powder with 15.0g sodium chloride, 15.0g potassium chloride and 1.5g sodium fluoride, heat to 1450℃ and hold for 5h under argon atmosphere, cool to room temperature, wash with deionized water, dry, ball mill and sieve to obtain boron-titanium-silicon-carbon pinned toughened whiskers.
[0060] Comparative Example 1
[0061] The difference between this comparative example and Example 1 is that no yttrium cerium zirconium aluminum silicon thermal shock stabilizing crystalline phase was prepared and added, and 4.0g of α-alumina micro powder was used to replace 4.0g of yttrium cerium zirconium aluminum silicon thermal shock stabilizing crystalline phase. The rest is the same as in Example 1.
[0062] Comparative Example 2
[0063] The difference between this comparative example and Example 1 is that boron-titanium-silicon-carbon pinned toughening whiskers are not prepared and are not added, and 3.25g of sintered corundum is used instead of 3.25g of boron-titanium-silicon-carbon pinned toughening whiskers. The rest is the same as in Example 1.
[0064] Comparative Example 3
[0065] The difference between this comparative example and Example 1 is that yttrium cerium zirconium aluminum silicon thermal shock stabilizing phase and boron titanium silicon carbon pinning toughening whiskers are not prepared and added. Instead, 4.0g of α-alumina micropowder is used to replace 4.0g of yttrium cerium zirconium aluminum silicon thermal shock stabilizing phase, and 3.25g of sintered corundum is used to replace 3.25g of boron titanium silicon carbon pinning toughening whiskers. The rest is the same as in Example 1.
[0066] The performance of the high-strength wear-resistant sintering plates obtained in Examples 1-3 and Comparative Examples 1-3 was tested.
[0067] The firing plates prepared in Examples 1-3 and Comparative Examples 1-3 were used as test samples. The number of samples in each group was no less than 5. Before the test, the samples were dried at 110°C for 6 hours and then cooled to 25°C in a desiccator for later use.
[0068] During the bulk density test, the firing plate sample was processed into a regular sample with flat edges and no obvious gaps on the surface. The dried mass was weighed using an electronic balance with an accuracy of 0.01g. The length, width and thickness of the sample were measured using a vernier caliper with an accuracy of 0.02mm. Three measurements were taken in each direction and the average value was taken. The volume of the sample was calculated, and the ratio of the dried mass to the sample volume was used as the bulk density.
[0069] During the room temperature flexural strength test, the sintered plate sample is cut into a long strip. The surface of the sample is polished and the burrs at the edges are removed. The sample is loaded using a three-point bending method with a span of 80 mm. The force-bearing surface of the sample is kept flat. The sample is loaded until it breaks. The maximum load is recorded. The room temperature flexural strength is calculated according to the sample width, thickness, span, and maximum load.
[0070] During the 1450℃ high-temperature flexural strength test, the strip specimen was placed in the high-temperature flexural strength testing device, heated to 1450℃ and held for 30 minutes. After the specimen temperature stabilized, a three-point bending load was applied with a span of 80 mm until the specimen broke. The maximum load was recorded, and the 1450℃ high-temperature flexural strength was calculated according to the specimen width, thickness, span and maximum load.
[0071] During the wear test, the bearing plate sample was processed into a plate-shaped specimen. The test surface was polished until flat, and after cleaning the surface powder, the mass before grinding was measured. Alumina abrasive was used to wear the same test surface. The wear load was 10N, the wear time was 30min, and the wear stroke was 1000m. After the wear was completed, the residual abrasive and powder on the surface were removed with a soft brush, and the mass after grinding was measured again. The difference between the mass before grinding and the mass after grinding was taken as the wear amount.
[0072] In the test of flexural strength retention rate after water-cooled thermal shock, the strip sample was placed in a furnace at 1000℃ for 30 minutes and then immediately immersed in 25℃ deionized water to cool to room temperature. This was considered one water-cooled thermal shock cycle. After 10 cycles, the sample was dried at 110℃ for 2 hours and then cooled to 25℃. The flexural strength after thermal shock was then determined according to the room temperature flexural strength test method. The flexural strength retention rate after 10 cycles of water-cooled thermal shock at 1000℃ was calculated by the ratio of the flexural strength after thermal shock to the room temperature flexural strength before thermal shock.
[0073] During the 1450℃ high-temperature load-bearing deformation test, the sintered plate sample was placed horizontally on a high-temperature resistant support with a support span of 100mm. A 2.0kg load was applied to the center of the sample. The loaded sample was then placed in a high-temperature furnace and heated to 1450℃ and held for 4 hours. After cooling to 25℃ in the furnace, the sample was removed and the maximum downward deflection at the center of the sample was measured using a measuring instrument with an accuracy of 0.01mm. This downward deflection was taken as the 1450℃ high-temperature load-bearing deformation. The arithmetic mean of the test results of the same group of samples was taken as the final result for each test item.
[0074] The performance test data above are shown in Table 1.
[0075] Table 1: Performance Test Results
[0076]
[0077] The test results in Table 1 above clearly show that the bulk density of Examples 1-3 is 2.86-3.02 g / cm³. 3 Overall, it was higher than the 2.76 g / cm³ of Comparative Example 3. 3 This indicates that the addition of yttrium cerium zirconium aluminum silicon thermal shock stabilizing crystalline phase and boron titanium silicon carbon pinned toughening whiskers is beneficial to improving the filling and sintering bonding between ceramic particles, making the internal structure of the sintering plate more compact.
[0078] The room temperature flexural strength of Examples 1-3 was 94-116 MPa, which was significantly higher than that of Comparative Example 3 (76 MPa), and also higher than that of Comparative Example 1 (92 MPa without the addition of the thermally shock stabilizing yttrium cerium zirconium aluminum silicon phase) and Comparative Example 2 (89 MPa without the addition of boron titanium silicon carbon pinned toughening whiskers). This indicates that both the thermally shock stabilizing yttrium cerium zirconium aluminum silicon phase and the boron titanium silicon carbon pinned toughening whiskers have the effect of improving the strength of the plate, and the strength improvement is more obvious when both are used together.
[0079] The high-temperature flexural strength of Examples 1-3 at 1450℃ was 34-43 MPa, which was higher than that of Comparative Example 1 (31 MPa), Comparative Example 2 (32 MPa), and Comparative Example 3 (25 MPa), indicating that the present invention improved the problem of rapid strength decay of the bearing plate under high-temperature load conditions.
[0080] The wear amount of Examples 1-3 was 0.09-0.15g, which was lower than that of Comparative Example 1 (0.16g), Comparative Example 2 (0.24g), and Comparative Example 3 (0.29g). In particular, compared with Comparative Example 2 (which did not add boron-titanium-silicon-carbon pinned toughening whiskers) and Comparative Example 3 (which did not add yttrium-cerium-zirconium-aluminum-silicon thermal shock stabilizing phase and boron-titanium-silicon-carbon pinned toughening whiskers), the wear amount was significantly reduced, indicating that boron-titanium-silicon-carbon pinned toughening whiskers can reduce particle shedding and improve the wear resistance of the plate surface.
[0081] The flexural strength retention rate of Examples 1-3 after 10 cycles of water-cooled thermal shock at 1000℃ was 78.2-86.1%, which was higher than that of Comparative Example 1 (69.4%), Comparative Example 2 (77.6%) and Comparative Example 3 (61.8%). This indicates that the thermally shock-stable crystalline phase of yttrium cerium zirconium aluminum silicon can improve the thermal shock stability of the particle interface and reduce the risk of thermal shock crack initiation and propagation.
[0082] The deformation under high temperature load of 1450℃ in Examples 1-3 was 0.14-0.27 mm, which was lower than that of Comparative Example 1 (0.29 mm), Comparative Example 2 (0.23 mm), and Comparative Example 3 (0.41 mm), indicating that the present invention can improve the dimensional stability of the firing plate under high temperature load.
[0083] Based on the above data, Examples 1-3 effectively solve the technical problems of insufficient strength, poor wear resistance, low strength retention rate after thermal shock, and large deformation under high temperature loads in existing bearing plates compared with Comparative Examples 1-3.
Claims
1. A method for preparing a high-strength wear-resistant sintered plate, characterized in that the steps include... include: S1. By weight, mix 35.0-50.0 parts sintered corundum, 18.0-28.0 parts fused mullite particles, 8.0-15.0 parts α-alumina micro powder, 6.0-12.0 parts silicon carbide micro powder, 3.0-8.0 parts zirconium oxide micro powder, 3.0-7.0 parts aluminum titanate powder, 3.0-8.0 parts calcined kaolin, 2.0-5.0 parts talc powder, and 0.5-2.0 parts magnesium oxide powder to obtain basic ceramic powder; add 2.0-6.0 parts yttrium cerium zirconium aluminum silicon thermal shock stabilized crystalline phase and 1.5-5.0 parts boron titanium silicon to the basic ceramic powder. Carbon nails are used to toughen whiskers, and mixing continues to obtain composite ceramic powder. 0.4-1.2 parts of polyvinyl alcohol are added to 8.0-16.0 parts of deionized water and stirred at 85-95℃. After cooling to room temperature, 4.0-9.0 parts of silica sol are added while stirring, and stirring continues. Then, 0.2-0.8 parts of sodium carboxymethyl cellulose, 0.5-1.5 parts of polyethylene glycol 400, and 0.1-0.5 parts of sodium polyacrylate are added and stirred to obtain a composite binder dispersion. The composite ceramic powder is added to the composite binder dispersion and mixed at 20-30℃ to form a clay, yielding a ceramic blank. S2. Press the ceramic blank into shape, dry it to obtain the firing plate blank; place the firing plate blank in the kiln, and heat it to 300-400℃ in air atmosphere and hold it at that temperature. Pre-reaction and sintering processes are carried out under an argon atmosphere, followed by cooling. The method for preparing the thermally shock-stabilized yttrium cerium zirconium aluminum silicon crystalline phase includes: A1. By weight, add 4.0-8.0 parts of yttrium hexahydrate, 6.0-12.0 parts of zirconium oxychloride octahydrate, 3.0-7.0 parts of cerium nitrate hexahydrate, and 12.0-20.0 parts of aluminum nitrate nonahydrate to 15.0-25.0 parts of deionized water and stir to obtain an aqueous solution of the metal salt; add 4.0-9.0 parts of tetraethyl orthosilicate to 20.0-35.0 parts of anhydrous ethanol and stir to obtain an alcoholic solution of tetraethyl orthosilicate; add the alcoholic solution of tetraethyl orthosilicate to the aqueous solution of the metal salt and stir to obtain a precursor solution; add 8.0-15.0 parts of citric acid and 10.0-18.0 parts of ethylene glycol to the precursor solution and stir at 70-85℃; adjust the pH to 6.0-8.0 with ammonia water and continue stirring to obtain a yttrium-cerium-zirconium-aluminum-silicon composite gel; A2. Dry the yttrium cerium zirconium aluminum silicon composite gel at 100-120℃ to obtain a dry gel; heat the dry gel to 450-550℃ in air atmosphere and keep it at that temperature, then heat it to 950-1100℃ and keep it at that temperature, cool it to room temperature, ball mill it, and sieve it. The method for preparing the boron-titanium-silicon-carbon pinned toughened whiskers includes: B1. By weight, mix 8.0-16.0 parts of tetrabutyl titanate, 20.0-35.0 parts of anhydrous ethanol and 2.0-5.0 parts of acetylacetone, and stir to obtain a titanium complex solution; mix 6.0-12.0 parts of boric acid, 5.0-10.0 parts of nano-silica, 3.0-7.0 parts of acetylene black, 6.0-14.0 parts of anhydrous glucose and 6.0-12.0 parts of deionized water to obtain a borosilicate carbon dispersion; add the borosilicate carbon dispersion to the titanium complex solution and stir at 45-60℃ to obtain a borosilicate carbon composite sol. B2. Dry and grind the boron-titanium-silicon-carbon composite sol to obtain precursor powder; mix the precursor powder with 8.0-15.0 parts of sodium chloride, 8.0-15.0 parts of potassium chloride and 0.5-1.5 parts of sodium fluoride, heat to 1400-1450℃ under argon atmosphere and hold at that temperature, cool to room temperature, wash with deionized water, dry, ball mill and sieve.
2. The method for preparing the high-strength wear-resistant sintered plate according to claim 1, characterized in that, In step S1, the stirring time at 85-95℃ is 30-60 minutes.
3. The method for preparing the high-strength wear-resistant sintered plate according to claim 1, characterized in that, In step S2, the pre-reaction treatment includes: heating to 700-900℃ and holding, then heating to 1250-1350℃ and holding; the sintering treatment includes: heating to 1450-1580℃ and holding.
4. The method for preparing the high-strength wear-resistant sintered plate according to claim 1, characterized in that, In step A1, the stirring time is 2-4 hours at 70-85℃.
5. The method for preparing the high-strength wear-resistant sintered plate according to claim 1, characterized in that, In step A2, the holding time for heating to 450-550℃ is 1-3 hours; the holding time for heating to 950-1100℃ is 2-4 hours.
6. The method for preparing the high-strength wear-resistant sintered plate according to claim 1, characterized in that, In step B1, the stirring time at 45-60℃ is 1-3 hours.
7. The method for preparing the high-strength wear-resistant sintered plate according to claim 1, characterized in that, In step B2, the temperature is raised to 1400-1450℃ and held for 2-5 hours.
8. A high-strength, wear-resistant, fire-resistant plate, characterized in that, The high-strength wear-resistant sintering plate is prepared by the method according to any one of claims 1-7.